Case report: A 3-year follow-up study of simultaneous bilateral total hip arthroplasty for Femoral head necrosis in a patient with Kashin-Beck Disease - Chen, Xiangyu; Liu, Haibin; Wang, Houqing; Zheng, Liqiang; Li, Jiayu; Yan, Lianqi (Frontiers in Surgery, 2022)
Abstract Introduction Kashin-Beck Disease（KBD）is an endemic disease predominantly affecting joint and skeletal muscle, predisposing the articular cartilage to degeneration and necrosis. Currently,staged total hip arthroplasty is a common surgical method for advanced femoral head necrosis from KBD, but there are no reports in the literature on simultaneous bilateral total hip arthroplasty（SB-THA）for patients with KBD. Case presentation A 42-year-old male from Shaanxi Province, an endemic area, had bilateral hip pain for 4 years, with hips inversion and a crossed gait. After preoperative preparation, a SB-THA was performed by a posterolateral approach. Postoperative medication and functional exercises were administered and the patient was followed up for at least 3 years after discharge. The patient's hip mobility, hip scores, and quality of life scores were recorded in detail during the follow-up. Result The patient stopped antibiotic treatment on the postoperative day-2, and all inflammatory indicators showed normal and started appropriate exercise, and the pain score decreased significantly. On postoperative day-7, the patient had gradually adapted to various forms of rehabilitation exercises. He was discharged from the hospital on the postoperative day-10 and continued to be followed up. From the preoperative period to the last follow-up, the patient's bilateral hip mobility and functional scores improved significantly, and no adverse events such as hip pain, prosthesis loosening or dislocation were found at the last follow-up. conclusion The patient's performance was satisfactory both intraoperatively and in the early postoperative period, but the hip scores and quality of life scores began to plateau or even decline from the third year after surgery to the last follow-up, probably due to the influence of further damage to articular cartilage in other parts of the body.